Government standard operating procedures a basic handbook. - Fellowship of Christians in Government (Philippines). (Quezon City Fellowship of Christians in Government, 2005)
A handbook that can serve as a guide to transaction procedures with different government offices and agencies in the Philippines like the DTI, BIR, NSO, DFA, LTO, etc.
It is the Fellowship of Christians in Government's intent that the Guidelines and/or standard operating procedures or policies (SOP's) of some government agencies contained here be useful to and easily understood by the public.
Keywords: Administrative agencies -- Philippines -- Handbooks, manuals, etc; Administrative agencies -- Philippines -- Rules and practice